O uso de materiais audiovisuais produzidos por zoológicos como ferramenta educativa para a conservação da fauna no ensino formal - Pereira, Gabriela Aparecida (2022)
The use of social media use has been growing every day specially the ones such as YouTube were the medias produce by zoo are getting more space each day. This arises an opportunity to use zoo videos in schools and spread the environmental education to several people. This study had the aim to identify trough content analysis, the main features of zoo videos posted on YouTube. We select fifty videos from the eight largest zoo channels of Brazil zoos on YouTube. They were transcript, and classified according to the central themes they presented, the categories of meaning attributed to biodiversity, sphere of values, scientific contents and forms of participation, views, and number of likes. The analysis obtained suggest that the most frequent themes on the videos were about zoo animal and their conservations projects. The categories of meaning most repeated were the one about the parks and human actions for conservation of the species, and the ones about general knowledge, concepts, and ideas about biodiversity. Regarding the spheres, the ones about of ethical and aesthetic values, were the most frequent. The most popular video had 140,793 views, and the most liked 2,200 likes, showing that the relevance of these contents can achieve on YouTube. The perceptions of educators about these videos were also collected through a structured questionnaire, and the data analyzed indicate that most of the teachers would use zoo videos in their classes, and the aspects that most caught the attention of these educators were the topics talked on the videos and the language used. They also reported that it was interesting to produce more videos covering the subjects about “Use of natural resources/Biodiversity Conservation” and “Biological Concepts”. The videos analyzed showed great potential for use in classroom, and to increase their popularity on YouTube, topics on natural resources and biodiversity conservation as well as biological concepts are recommended. For a more critical approach on these videos, the biodiversity could be explored more widely, were its seen as a whole, and the sphere of “forms of participation” can be more explored on these videos. The results indicate the possibility of enhancement on the production of new video materials, their potential to be used on formal and non-formal educational contexts as well as on the spread of biodiversity knowledge.